2007
DOI: 10.11150/kansenshogakuzasshi1970.81.173
|View full text |Cite
|
Sign up to set email alerts
|

Largest Outbreak of Legionellosis Associated with Spa Baths

Abstract: In July 2002, a large outbreak of legionellosis occurred in a bathhouse with spa facilities in Miyazaki Prefecture. Among the visitors, 295, including suspected cases had pneumonia and/or symptoms of fever, coughing, etc. Of these, 37% were hospitalized and 7 died. Clinical samples from 95 mainly inpatients were collected and microbiologically tested at our laboratory. Legionella pneumophila serogroup (SG) 1 was isolated from 3 of 24 in sputum culture, and none of the 3 had been treated effectively with antibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The urine antigen test may fail to detect bacterial antigens in all patients with Legionnaires' disease, especially when samples are obtained just after the development of the disease. 15 Kawano et al 16 reported that serum antibodies to L. pneumophila SG1, without any other serogroups, were detected in 5 of 66 patients in the same outbreak. They 16 also reported that several other patients were positive for the antibody to L. dumoffi i, which is not detectable by the urinary antigen test.…”
Section: Discussionmentioning
confidence: 96%
“…The urine antigen test may fail to detect bacterial antigens in all patients with Legionnaires' disease, especially when samples are obtained just after the development of the disease. 15 Kawano et al 16 reported that serum antibodies to L. pneumophila SG1, without any other serogroups, were detected in 5 of 66 patients in the same outbreak. They 16 also reported that several other patients were positive for the antibody to L. dumoffi i, which is not detectable by the urinary antigen test.…”
Section: Discussionmentioning
confidence: 96%
“…1) (https://www.niid.go.jp/ niid/ja/survei/2085-idwr/ydata/7310-report-ja2016-20.html), with the diagnosis of urinary antigen being prevalent. Several outbreaks of Legionnaires' disease associated with public bath facilities have occurred (5)(6)(7)(8)(9)(10), and bathing facilities were found to be the main source of infection in Japan (8), although most such facilities had circulation systems fitted with filters and used hot spring water. Even for sporadic cases, infection source surveys were conducted by some public health centers, and bathing facilities could be identified as the source of infection by using molecular epidemiology (11,12).…”
mentioning
confidence: 99%
“…Sporadic Legionella infections, rather than outbreak cases, still account for most Legionella infections in Japan (61,62). However, outbreaks of LD associated with communal bathing facilities also remain a regularly occurrence (63)(64)(65)(66)(67)(68), such facilities remain the main source of infection in Japan, even though most operate with filtered circulation systems installed and use natural geothermal water (69).…”
Section: Specific Situations In Japanmentioning
confidence: 99%